1987
DOI: 10.1111/j.1471-4159.1987.tb02913.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Cerebroventricular Metabolism of [125I]Angiotensins in the Spontaneously Hypertensive Rat

Abstract: This study was designed to evaluate the hypothesis that impaired brain angiotensin signal termination contributes to the sustained blood pressure elevations noted in the genetically hypertensive rat model of human essential hypertension. A technique that combined the intracerebroventricular injection of [125I]angiotensins, followed by focused microwave fixation to stop all peptidase activity and subsequent HPLC analyses, was used for determining half-lives of [125I]angiotensin II and [125I]angiotensin III in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…The longer half-life of [Ile'l-Ang I1 in neuron-enriched cells from SHR is in good agreement with findings of delayed cerebroventricular metabolism of "'I-labeled Ang I1 in SHR (Harding et al, 1986;Wright et al, 1987). In contrast to these studies, we could not confirm the very short half-lives (<1 min in our preparation) of intracerebroventricularly administered 251-labeled Ang I1 and I11 (Harding et al, 1986;Wright et al, 1987). Differences in the experimental protocols, such as the use of intact animals, 12'I-labeled peptides, and substrate enzyme ratios influencing the kinetics, may be critical in this regard.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The longer half-life of [Ile'l-Ang I1 in neuron-enriched cells from SHR is in good agreement with findings of delayed cerebroventricular metabolism of "'I-labeled Ang I1 in SHR (Harding et al, 1986;Wright et al, 1987). In contrast to these studies, we could not confirm the very short half-lives (<1 min in our preparation) of intracerebroventricularly administered 251-labeled Ang I1 and I11 (Harding et al, 1986;Wright et al, 1987). Differences in the experimental protocols, such as the use of intact animals, 12'I-labeled peptides, and substrate enzyme ratios influencing the kinetics, may be critical in this regard.…”
Section: Discussionsupporting
confidence: 87%
“…This finding is in contrast to previous work reporting a faster turnover of Ang I1 in SHR after central CE inhibition (Ganten et al, 1983). The longer half-life of [Ile'l-Ang I1 in neuron-enriched cells from SHR is in good agreement with findings of delayed cerebroventricular metabolism of "'I-labeled Ang I1 in SHR (Harding et al, 1986;Wright et al, 1987). In contrast to these studies, we could not confirm the very short half-lives (<1 min in our preparation) of intracerebroventricularly administered 251-labeled Ang I1 and I11 (Harding et al, 1986;Wright et al, 1987).…”
Section: Discussionsupporting
confidence: 67%
“…Considerable evidence suggests that dysfunction of the central renin-angiotensin system, in particular the degradation of angiotensin [45,46], contributes to the observed increase in arterial pressure [12,40,47], foodrelated drinking [20], drinking response to i.c.v. adminis tered AIII [40,47] and salt appetite [11,28] in this strain.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was evaluated in the present study, utilizing a treatment schedule we designed previously [3,6,7,22,23] for the evaluation of endogenous neuropep tide activity. We also delineated whether differential responses existed in the spontaneously hypertensive (SH) and its normotensive control rats, since a dysfunction of central aminopeptidase activity, leading to an impair ment of the termination of angiotensin signals, has been suggested to contribute to the blood pressure abnormality of the SHRs [45][46][47]. Our results revealed that the endog enous brain AIII may not be tonically involved in fluid homeostasis.…”
Section: Introductionmentioning
confidence: 97%
“…We suspected a disruption in brain aminopeptidase activity in the SHR [87, 88]. To test this hypothesis replacement Glu-AP was i.c.v.-infused in order to promote the hydrolysis of AngII to AngIII.…”
Section: The Emergence Of Angiii and Apa As Key Factors In Sustainmentioning
confidence: 99%